PENINGKATAN NILAI KARAKTER GOTONG ROYONG MELALUI PEMANFAATAN MEDIA VIDEO ANIMASI PADA SISWA KELAS 3 SD NEGERI 3 PANDEAN NGEMPLAK BOYOLALI - Sinatrya Tyas Puspita; Suyitno; Kiswoyo (STKIP Subang, 2026)
Puspita, Sinatrya Tyas. 2026. Improving Mutual Cooperation Character Values Through the Use of Animated Video Media in 3rd Grade Students of SD Negeri 3 Pandean Ngemplak Boyolali. Thesis. Elementary School Teacher Education Study Program, Faculty of Education, Universitas PGRI Semarang.This research is motivated by the low mutual cooperation (gotong royong) character values among 3rd-grade students at SD Negeri 3 Pandean, as evidenced by students' egocentric attitudes, lack of cooperation in groups, and the use of conventional and monotonous learning methods. The main objective of this study is to determine the improvement of mutual cooperation character values through the utilization of animated video media in 3rd-grade students of SD Negeri 3 Pandean Ngemplak Boyolali during the odd semester of the 2025/2026 academic year.This research is a Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 29 students from the 3rd grade. Data collection techniques were carried out through behavioral observations, knowledge tests, and skill assessments. The media used in the intervention included the animated video